Energy efficient sensor nodes placement using Territorial Predator Scent Marking Algorithm (TPSMA) - Abidin H.Z.; Din N.M. (Institute of Physics Publishing, 2023)
The positions of sensor nodes in a Wireless Sensor Network (WSN) must be able to provide maximum coverage with a longer lifetime. This paper proposed a sensor node placement technique that utilizes a new biologically inspired optimization technique that imitates the behavior of territorial predators in marking their territories with their odors known as Territorial Predator Scent Marking Algorithm (TPSMA). The TPSMA deployed in this paper uses the maximum coverage ratio as the objective function. The performance of the proposed technique is then compared with other schemes in terms of uniformity and average energy consumption. Simulation results show that the WSN deployed with the proposed sensor node placement scheme consumes lower energy compared to the other two schemes and is expected to provide longer lifetime. Published under licence by IOP Publishing Ltd.